4 - Putting Oil First? Some Ethnographic Aspects of Petro leum-related Land Use Contro versies in NigeriaPutting Oil First? Some Ethnographic Aspects of Petro leum-related Land Use Contro versies in Nigeria - Wilson Akpan (African Sociological Review, 2004)
This arti cle exam ines, based on recent ethnographic data, one of the lesser known pro cesses through which petro leum oper ations sus tain social con flict in Nige ria. Focussing on what has come to be termed ‘em inent domain abuse’ by the inter na tional envi ron men tal jus tice com munity, the arti cle reveals the char ac ter of petro leum oper ations in a num ber of com mu ni ties in Nige ria’s oil-producing region. The arti cle relates the practices of the trans national oil com panies, the dis position of the reg ulatory author ities, and the oppositional dis courses of ordi nary peo ple in the oil com mu ni ties to the laws gov erning land use and min eral own ership in the coun try.